(untitled) (Journal of Medical & Health Sciences Review, 2025)
Live feeds like phytoplankton and zooplankton serve as the best starter meal for a number of aquatic organisms. The proposed study was conducted for 60 days to check out the effect of dietary replacement of commercial feed with Moina on meat quality and antioxidant enzymes in Catla catla. Total of 200 fish specimens were collected and divided into 4 experimental groups T0, T 1, T2 and T3 in triplicates. T0 was the control group given 100% basal diet while T l, T2 and T3 were the experimental groups given three graded levels of Moina 10%, 20% and 30% respectively. Meat quality parameters such as moisture content, crude ash, crude fat, crude protein and antioxidant enzyme activity in terms of catalase and peroxidase were measured at the end of the trial. The average value of moisture content was higher in T3 which was 76.8 given 30% Moina showed the highest average value. The average value of crude ash in T3 which was 16.06 and given 30% Moina showed the highest average value. The average value of lipid content was higher in T3 which was 77.29 given 30% Moina showed the highest average value. The average value of catalase was higher in liver, gills T3 52.86, T3 16.04 respectively, which was given 30% Moina. The average value of peroxidase in liver and gills was higher in T3 13.7, T3 47.79, which was given 30% Moina. The data was obtained and subjected to statistical analysis by applying one-way ANOVA that showed highly significant difference as the p-value was found to be equal to 0.000 (p<0.05). The replacement of commercial feed by Moina has the potential to increase the meat quality and antioxidant enzymes activity.